Pemberdayaan Masyarakat dalam Penyediaan Air Bersih melalui Metode Desalinasi Sistem Termal Surya - Noorce C Berek; Christina R Nayoan; Serlie K A Littik; Ben V Tarigan (Yayasan Sumber Daya Manusia Cerdas, 2025)
Clean water needed by the entire community is not evenly distributed across various regions in NTT, especially in Enoraen Village, East Amarasi District, Kupang Regency, which is a coastal area. Clean water can be provided in this area through solar thermal desalination. This community service aims to improve the congregation's ability to recognize clean water that is suitable for drinking, as well as to train the congregation to use and maintain desalination equipment to produce clean water. The methods used are lectures and training, as well as periodic guidance. This community service activity consists of education related to clean water and drinking water, training in the use and maintenance of desalination equipment, and assistance for approximately 6 months. The results of the activity showed an increase in the congregation's knowledge in recognizing the quality of clean water suitable for drinking. In addition, the congregation was able to use the desalination equipment, as demonstrated by an increase in the amount of water produced by the equipment after 7 days of use. Assistance in the use of solar thermal desalination equipment is still being provided, particularly to assess the congregation's ability to maintain the desalination equipment so that its use can help in the provision of clean water in the congregation.